Pola Sikap Dan Perilaku Politik Perempuan Anggota Dprd Kabupaten Jember Dan Bondowoso Terhadap Policy Making Berperspektif Gender: Attitudes And Political Behavior Of Women Members Of The Regional Representative Council Of Jember And Bondowoso Towards Gender-Sensitive Policy Making - Sofyan Hadi (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2015)
It took a long time of hard work for the women of Jember and Bondowoso to fight for their representation in political institutions, and even now, the representation of women in parliament is still far from proportional to the female population in both cities. The long debate over whether women are fit to sit in parliament has not stopped, despite various movements and protests emerging. This is undoubtedly caused by the patriarchal cultural system that is deeply rooted in society, especially in rural areas where the majority of the population is Madurese and Javanese. However, if we look at the bigger picture, ignoring gender issues means ignoring social facts and the daily experiences of the community, where the oppression of women is a chain of injustice that then impacts the lives of the community, including men from poor and minority groups. Finally, relying on the minority of female council members in Jember and Bondowoso, it is hoped that the attitudes and political behavior of these modern heroines in parliament can represent the realization of local regulations and policies that prioritize the interests and rights of women. Butuh cucuran keringat dalam waktu lama bagi perempuan Jember dan Bondowoso untuk memperjuangkan keterwakilan mereka di lembaga politik yang fenomenanya hingga saat ini keterwakilan perempuan di parlemen masih berbanding jauh dengan populasi perempuan di kedua kota tersebut. Perdebatan panjang menyoal pantas tidaknya perempuan duduk di kursi parlemen rupanya belum berhenti meskipun bermacam gerakan dan aksi protes mencuat di permukaan. Hal ini tentunya diakibatkan oleh sistem budaya patriarkhi yang mengakar pada masyarakat utamanya daerah pedesaan yang mayoritas bersuku Madura dan Jawa. Padahal jika ditarik benang merahnya, pengabaian isu gender berarti menisbikan fakta sosial dan pengalaman keseharian masyarakat dimana keterpurukan perempuan merupakan rantai kondisi ketidakadilan yang kemudian berdampak pada hidup masyarakat, termasuk laki-laki dari kelompok miskin dan minoritas. Akhirnya bersandar pada minoritas anggota dewan perempuan di Jember dan Bondowoso, semoga pola sikap dan perilaku politik srikandi-srikandi modern di parlemen ini bisa mewakili terwujudnya peraturan daerah dan kebijakan-kebijakan yang menitik beratkan pada kepentingan dan hak-hak kaum perempuan.